Impact of conservation tillage practices in rice-blackgram cropping system - Subrahmaniyan, K; Parthipan, T; Rajavel , M; Veeramani, P (Bangladesh Journal of Botany, 2024)
Field experiments were conducted with two tillage practices in rice (Puddled and Non- puddled) during rainy season and three seed priming methods (Bio- seed priming with Rhizobium, hydropriming and no seed priming) and two foliar spray (2% DAP and 2% urea) during post rainy seasons in blackgram. The results indicated that the soil penetration resistance was found to be lesser in the soils of non-puddled tillage. The rice yield reduction due to NPTR was non-significant (less than 3 per cent). However, the soil penetration resistance was higher with the soils of blackgram sown as succeeding crop in the PTR. The blackgram yield obtained under NPTR was 10.6 per cent higher than PTR system. Bio seed priming with Rhizobium increased the yield by 26.0 per cent over no seed priming. The study indicated that NPTR showed a positive impact on the yield in the rice-blackgram relay cropping system. Bangladesh J. Bot. 53(3): 519-525, 2024 (September)